SWOT Analysis: How to Promote Halal Tourism in Aceh? - Ricky Alfanda; Pratiwi Dwi Suhartanti (Universitas Sebelas Maret, 2017)
This study aims at describing potentials of halal tourism destination in Aceh by analyzing readiness of tourism destination through perceptions of tourism travel agents and tourists in developing halal tourism in Aceh. This study also produces right strategies to develop halal tourism by tourist destination characteristics. The data and information collection is done through FGD (Focus Group Discussion), in-depth interview and distribution of questionnaire to 327 tourists in Aceh. Based on the result of the study, Aceh is quite optimal in launching halal tourism as its tourism product yet there should be more improvements and strategies for increasing tourist attraction. The result of this study is expected to help the government of Aceh and tourism travel agents in increasing halal tourism potentials and setting strategies in developing halal tourism potentials so they could attract tourists to have halal tourism in Aceh or visit Aceh.